Pengaruh Manajemen Talenta terhadap Employee Engagement dan Work From Home sebagai Variabel Moderasi - Christian Daniel Mende; Yustina Erti Pravitasmara Dewi (Jurnal Administrasi Bisnis, 2021)
The work from home phenomenon due to the pandemic triggers doubts on the governance of employee talent, including efforts to maintain its attachment or called employee engagement. Reduced direct interaction between employees or between leaders and employees leads to doubts on attachment to the organization, especially if it is associated with employees in Generation Y. Generation Y is expected to show the same employee engagement between working in the office or when doing its work from home. This research aims to test the relationship of talent management to employee engagement generation Y with work from home as a moderation variable. The sampling technique was accidental sampling of 201 Generation Y employees in Indonesia who practice work from home were involved as research samples. Data analysis techniques used analysis based on SEM (Structural Equation Model) with an evaluation of measurement and structural models for hypothesis testing. The results of this study indicate that talent management has a significant and positive effect on generation Y employee engagement and work from home has no significant and positive effect on the relationship between talent management and generation Y employee engagement.Fenomena work from home akibat pandemi mendorong terjadinya perubahan pada tata kelola karyawan, termasuk mempertahankan keterikatannya atau disebut dengan employee engagement. Karyawan yang memiliki keterikatan dengan organisasinya dikenali dengan perilaku sadar, waspada yang secara emosi terhubung dengan organisasi dan berkomitmen melakukan perannya dengan kemampuan terbaiknya. Generasi Y diharapkan menunjukkan employee engagementnya ketika melakukan pekerjaannya dari rumah. Penelitian ini bertujuan untuk menguji hubungan manajemen talenta terhadap employee engagement generasi Y dengan work from home sebagai variabel moderasi. Sebanyak 201 karyawan Generasi Y di Indonesia yang mempraktikkan work from home terlibat sebagai sampel penelitian. Teknik analisis data menggunakan analisis berbasis SEM (Structural Equation Model) dengan evaluasi model pengukuran dan struktural untuk uji hipotesis. Hasil penelitian ini menunjukkan manajemen talenta berpengaruh signifikan dan secara positif terhadap employee engagement generasi Y dan work from home berpengaruh tidak signifikan dan secara positif terhadap hubungan antara manajemen talenta dan employee engagement generasi Y.